Vandetanib Tumor Shrinkage in Metastatic Medullary Thyroid Cancer Allowing Surgical Resection of the Primary Site: A Case Report. Issue 5 (July 2019) - Milner, Thomas D.; Ronghe, Milind; Shaikh, Mohamad G.; MacGregor, Fiona B.; Reed, Nicholas
Abstract : Vandetanib has been shown to improve progression-free survival in adults with advanced medullary thyroid cancer. This article describes a pediatric patient with metastatic medullary thyroid cancer secondary to sporadic multiple endocrine neoplasia 2B, treated with vandetanib. At presentation, he had an inoperable primary tumor, with carotid encasement, and pulmonary metastases. Vandetanib induced a significant response: calcitonin and carcinoembryonic antigen levels both fell considerably, primary tumor maximal diameter decreased by 68%, and pulmonary metastases became no longer detectable. This allowed surgical resection of the primary tumor. The patient remains well after over 6 years of vandetanib therapy, with no treatment toxicity.